Does Entrepreneurship Education Affect Pre-start-up Behavior in Malaysia? A Multi-Group Analysis Approach - Othman, Nor Hafiza; Othman, Norasmah; Juhdi, Noor Hasni (Frontiers in Psychology, 2022)
This study investigates the moderating effect of students’ programmes on entrepreneurship education aimed at pre-start-up and its effect on the students’ behavior. This study also attempts the level of entrepreneurship education and pre-start-up behavior among students. A survey was carried out among 441 final year students, including 214 students from business programmes, and 227 students from non-business programmes. Data were analysed using IBM SPSS 22 and SmartPLS 3.3.0, to perform descriptive and multi-group analysis (MGA), including assessment of measurement invariance of the composite model (MICOM). The results reveal that all direct relationships were supported. It was also found that student programmes do have a moderating effect on the relationship between entrepreneurship education and pre-start-up behavior. Furthermore, the results discovered that risk control is a crucial component of entrepreneurship education and should be highlighted in the curriculum. This study contributes to the literature by considering student programmes as a moderator, a comparatively new factor in the pre-start-up behavior among university students at the tertiary level. Therefore, entrepreneurship education must be properly designed, and the co-curriculum must be properly organized, so that entrepreneurship will be the preferred career choice in the future.